Eksistensi Nilai Siri’ dan Pesse dalam Praktik Hukum Adat Masyarakat Bugis-Makassar: Suatu Kajian Sosio-Legal - Dyah Auliah Rachma Ruslan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Siri’ and Pesse are the foundational ethical and legal values of the Bugis-Makassar community, shaping social behavior, interpersonal relations, and traditional dispute resolution mechanisms. This study aims to examine how these values persist and remain functional within contemporary customary legal practices, despite the pressures of modernization, state law, and rapid socio-cultural change. Employing a socio-legal approach, the research explores the interaction between customary norms and formal legal structures through in-depth interviews, field observations, and analyses of adat documents. The findings reveal that Siri’ operates as a principle of honor that legitimizes social and legal actions, while Pesse embodies collective empathy that reinforces solidarity and social equilibrium. These values not only influence the resolution of familial and communal disputes but also shape adat-based mediation models that are perceived by local communities as more just and effective than formal legal mechanisms. Although state law provides a more standardized regulatory framework, Siri’ and Pesse continue to function as strong moral guidelines and remain central references in the pursuit of substantive justice. The study concludes that the existence of Siri’ and Pesse has not diminished; instead, these values have transformed to adapt to evolving legal contexts and societal dynamics. These findings contribute to a deeper understanding of the interaction between customary law and state law within Indonesia’s multicultural society.